CONSENSUS REPORT: Recognizing non‐melanoma skin cancer, including actinic keratosis, as an occupational disease – A Call to Action. (April 2016) - John, S.M.; Trakatelli, M.; Gehring, R.; Finlay, K.; Fionda, C.; Wittlich, M.; Augustin, M.; Hilpert, G.; Barroso Dias, J. M.; Ulrich, C.; Pellacani, G.
Abstract: Non‐melanoma skin cancer (NMSC) is by far the most common cancer diagnosed in westernized countries, 1 2 3 4 5 and one of the few almost preventable cancers if detected and treated early as up to 90% of NMSC may be attributed to excessive exposure to ultraviolet radiation.6 The incidence of NMSC is increasing: 2–3 million people are diagnosed worldwide annually, with an average yearly increase of 3–8% among white populations in Australia, Europe, the US and Canada over the last 30 years.2 3 4 5 7 The link between solar ultraviolet (UV) radiation and certain forms of NMSC is clearly recognized.8 9 It is estimated that outdoor workers are exposed to an UV radiation dose 2–3 times higher than indoor workers, 8 and there is a growing body of research linking UV radiation exposure in outdoor workers to NMSC: Occupationally UV‐exposed workers are at least at a 43% higher risk of basal cell carcinoma (BCC) and almost doubled risk of squamous cell carcinoma (SCC) compared to the average population, with risk increasing with decreasing latitude10 11 12 . The risk for BCC, SCC and actinic keratosis (AK) among workers who have worked outdoors for more than 5 years is 3‐fold higher than the risk among those with no years of working outdoors12 13 . Primary prevention, early detection, treatment and regular follow‐up of skin cancer (NMSC and melanoma) are shown to be beneficial from a health economic perspective.14 15 16 17 Action is needed at international, European and national level to legislate for recognizing AK and NMSC as an occupational disease, which has the potential to improve access to compensation and drive preventative activities. This report is a Call to Action for: The engagement of key stakeholders, including supranational institutions, national governments, trade organizations, employers, workers and patient organizations to drive change in prevention and protection of at‐risk groups. Employers should be obliged to prevent outdoor worker's UV exposure from exceeding limit values, and to implement occupational skin cancer screening programmes among the at‐risk workforce. Educational programmes for the outdoor workforce are needed to improve health literacy and drive behavioural change. Nationally, steps to improve notifications and surveillance of skin cancers through both occupational services and public health programmes are required. Future research activities should focus on the precise definition of at‐risk groups among outdoor workers through increased data gathering, including UV‐dosimetry, and evaluation.